IMPLEMENTASI MODEL MANAJEMEN STRATEGI DAN OPERASIONAL BERBASIS KINERJA LEMBAGA PENDIDIKAN - usman; Imam Makruf (Merwin Publisher, 2024)
This article discusses implementing performance-based strategic and operational management models in educational institutions, especially in the face of global challenges and environmental changes. You explain that education is the greatest investment in shaping the future of individuals and society. In the context of globalization, education must play a role in maintaining societal values and mitigating the negative impacts of globalization. The main benefits of education are intellectual development, the formation of values and ethics, and the improvement of the quality of life. To achieve these goals, strategic and operational management are important in the management of educational institutions. With strong strategic and operational management, academic institutions can become centers of learning excellence, highly competitive, and play an active role in facing future challenges. Goal focus, transparency, and accountability are the keys to success, which can help educational institutions achieve outstanding achievements and contribute to nation-building. This approach demonstrates the realisation of the importance of good management in advancing education and preparing individuals for a better future.